(adsbygoogle = window.adsbygoogle || []).push({}); Fact: If A and C are subsets of R, let AC={ac: a E A, c E C}. If A and C are bounded and A and C consist of strictly positive elements only, then sup AC = supA supC.

I am trying to understand and prove this fact, and this is what I've got so far...

A, C bounded => supA, supC exist (by least upper bound axiom)

0<a≤supA for all a E A

0<c≤supC for all c E C

=> 0<ac≤supA supC for all ac E AC

=> supA supC is an upper bound of AC

=> supAC≤supA supC

But how can we prove the other direction? I think we somehow have to use the fact "for all ε>0, there exists a E A such that sup A - ε < a."

At the end, we have to show that for all ε>0, supA supC - ε is NOT an upper bound for AC. But I'm not sure how it is going to work out here in our case.

Does anyone have any idea?

Thanks for any help!

**Physics Forums | Science Articles, Homework Help, Discussion**

Join Physics Forums Today!

The friendliest, high quality science and math community on the planet! Everyone who loves science is here!

The friendliest, high quality science and math community on the planet! Everyone who loves science is here!

# Show: sup AC = supA supC

**Physics Forums | Science Articles, Homework Help, Discussion**